ACURÁCIA DO MÉTODO DE PRESSLER E FATOR DE FORMA NA ESTIMAÇÃO DO VOLUME DE ÁRVORES DE TECTONA GRANDIS L. f. - SILVA, Gilson Fernandes da; OLIVEIRA, Onair Mendes de; MENDONÇA, Adriano Ribeiro de; FRAGA FILHO, Clayton Vieira (Brazilian Journal of Biometrics, 2017)
The aim of this paper was to verify the accuracy of Pressler’s method in the estimation of the individual volume of teak trees (Tectona grandis L. f.), scaled by using the Bitterlich’s relaskop. The database for this study consisted of 45 sample trees standing scaled by absolute isolation of the trunk and also by the Pressler’s method. After sampling, comparison tests were made by using the Leite and Oliveira´s test between the volume obtained with the traditional cube and the volume obtained by both the Pressler’s and Form Factor methods. The analyzes indicated that the method provides estimates of the volume by Pressler’s method closer to that obtained with traditional scaling, however slightly biased. Then, the Schumacher-Hall volumetric model was fitted to compare methods of scaling by Pressler and traditional. The fitted model, from the volume obtained by each method, was submitted to the model identity test. The results of the F test showed that there is identity among the parameters estimated in the model. Thus, one can say that the Schumacher-Hall model can be fitted from the volume data obtained by Pressler’s method.